Checkpoint inhibitors in advanced lung cancer - Shenoy, Casie S.; Kosty, Michael P. (Translational Cancer Research; Vol 6, No 1 (February 27, 2017): Translational Cancer Research (Focused Issue: Advances on Clinical Immunotherapy), 2017)
Metastatic lung cancer is often rapidly fatal even with cytotoxic chemotherapy treatment. The interaction of malignant cells with the immune system at the level of checkpoint proteins on T cells, has proven to be an effective novel target. Several so-called checkpoint inhibitors have since been developed and demonstrate benefit after chemotherapy failure, and in some cases, show benefit as first line treatment for advanced or metastatic lung cancer. This review will highlight the notable studies involving checkpoint inhibitors in advanced lung cancer.